Cattle in the Flint Hills - Jim Hoy (Symphony in the Flint Hills, 2009)
The Flint Hills are often referred to as "steer country" rather than "cow country," a distinction that refers to the practice of putting stocker cattle (i.e., steers and heifers intended for beef) on summer grass rather than keeping permanent cow herds (i.e., mother cows intended for raising calves, which will themselves become stockers - transient cattle as opposed to fulltime residents, in other words.
Keywords: cows; cattle; steer; ranching; farm; farmer; graze; grass; grassland; prairie; season; domestic; drives; Council Grove; country